Legal Protection of Innovations in the Regime of Commercial Secrets, Industrial Property: Comparative Analysis - L. D. Rudenko (Bulletin of Kharkiv National University of Internal Affairs)
The author of the article presents a comparative legal analysis of trade secret and industrial property regimes. Based on the analysis, the following distinctive features of legal regimes of trade secrets and industrial property are identified. The legal regime of industrial property provides strict criteria for the qualification of certain innovations as inventions, utility models, industrial designs. On the contrary, any commercially valuable innovations can be protected in the mode of trade secret. The legal regime of industrial property is a legal monopoly, as it provides the receipt of a security document (patent, declaratory patent). The trade secret regime is provided by a de facto monopoly, as it is ensured by the application of certain protective measures. The regime of industrial property rights presupposes the existence of both personal non-property and property exclusive rights. The trade secret regime provides only exclusive property rights. It has been identified that a common issue for both industrial property rights and trade secrets is the controversial application of "binding clauses" in licensing agreements, as they are contrary to the rules of fair competition. It is noted that the use of trade secrets to protect innovations is appropriate at the stage of development, mass production. When commercializing innovations, it is advisable to apply the regime of industrial property rights.